Magnitude and factors associated with anxiety and depression among patients with breast cancer in central Ethiopia: A cross-sectional study - Belay, Winini; Labisso, Wajana Lako; Tigeneh, Wondemagegnehu; Kaba, Mirgissa; Haileselassie, Werissaw (Frontiers in Psychiatry, 2022)
Abstract Background: Patients with breast cancer are assumed to be exposed to anxiety and depression, while little is known about the epidemiology and underlying factors in resource-constrained countries. Hence, we aimed to assess the prevalence and predictors of anxiety and depression among breast cancer patients in Ethiopia. Method: Institutional based cross-sectional study was conducted among patients with breast cancer who were attending treatment at the Oncology Center of the Tikur Anbessa Specialized Hospital, the largest referral teaching hospital in Ethiopia. The Hospital Anxiety and Depression Scale (HDAS) was used to evaluate anxiety and depression status of the participants and a structured questionnaire was used to collect sociodemographic, socioeconomic, and clinical data of the participants. Medical records of the participants were reviewed to collect and correlate information about the grade and stage of the cancer. Analysis was done using STATA 15.1. Result: The study included 333 randomly selected participants, of which 35.4% were on stage III and 33% stage II, and 67.9% were on chemotherapy and surgery. Prevalence of anxiety and depression were 60.7% and 58.6%, respectively. Having no emotional support (Adjusted odds ratio [AOR]=2.48, 95% CI: 1.17, 5.24), poor patient-provider interaction (AOR=2.70, 95% CI: 1.73, 4.21), poor financial support (AOR=2.54, 95% CI: 1.66, 3.90) were significant predictors of anxiety. Young age (AOR=1.25, 95% CI: 1.04, 1.52), having no emotional support (AOR= 8.66, 95% CI: 3.84, 19.54), poor patient-provider interactions (AOR= 2.52, 95% CI: 1.58, 4.02) and poor financial support (AOR=2.78, 95% CI: 1.79, 4.33) were significant predictors of depression. Conclusion: In this study, the prevalence of anxiety and depression were high among patients with breast cancer, and the lack of emotional and financial support and poor patient-provider interactions were significant predictors of anxiety and depression among this group of patients. Patients with cancer need regular screening for mental health and better emotional support from their healthcare providers and families to prevent and early treat anxiety and depression.